2014
DOI: 10.1155/2014/235619
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Branched-Chain Amino Acid Supplementation in Human Diseases

Abstract: The branched-chain amino acids (BCAAs), namely, valine, leucine, and isoleucine, are indispensable amino acids required for body protein synthesis. Unlike other amino acids, the BCAAs are primarily catabolised in the extrahepatic tissues. The BCAAs play role in regulation of protein synthesis and turnover as well as maintenance of the body glutamate-glutamine level. In strenuous and traumatic conditions, the BCAAs are oxidized which limits their availability in tissues. Such condition affects the body glutamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 65 publications
(77 reference statements)
0
32
0
4
Order By: Relevance
“…BCAAs play vital roles in regulation of protein synthesis and maintenance of glutamate-glutamine levels in the body. BCAAs are oxidised during high-energy-demanding and stressful conditions, and as a result, limit their accessibility in body tissues, which in the long run upsets mechanisms controlling the synthesis of proteins and body glutamate-glutamine pool [6].…”
Section: Branched-chain Amino Acidsmentioning
confidence: 99%
See 4 more Smart Citations
“…BCAAs play vital roles in regulation of protein synthesis and maintenance of glutamate-glutamine levels in the body. BCAAs are oxidised during high-energy-demanding and stressful conditions, and as a result, limit their accessibility in body tissues, which in the long run upsets mechanisms controlling the synthesis of proteins and body glutamate-glutamine pool [6].…”
Section: Branched-chain Amino Acidsmentioning
confidence: 99%
“…Several studies have reported that when BCAA supplements are administered, patients experience improvements in health, although there are some disease conditions where BCAAs showed no efects. However, increased levels of BCAAs in the body have been observed to be involved in disease pathology [6].…”
Section: Branched-chain Amino Acidsmentioning
confidence: 99%
See 3 more Smart Citations